"Tout le luxe de mise en scène": l'eccezionale eredità scenografica di Albert Dubosq (1863-1940) - Forment, Bruno 1978-; Il secolo di Mercedes Viale Ferrero: convegno internazionale di studi Turin 10-13 April 2024 (Aula Magna della Cavallerizza Università di Torino, Dipartimento di Studi Umanistici, Dipartimento di Studi Storici, 2023)
This paper explores the remarkable scenographic legacy of Albert Dubosq, a prolific painter-decorator whose career encompassed over 466 theatrical productions across Belgium, France, the Netherlands, Austria-Hungary, and the UK. Unlike many of his peers, Dubosq left behind a unique and tangible corpus: a vast collection of full-scale stage sets preserved in Courtrai, Belgium, and over 800 maquette elements rediscovered in Grenoble. These materials reveal Dubosq’s vibrant pleinairist aesthetic and innovative responses to the evolving stage technologies of the fin-de-siècle.This presentation examines Dubosq’s collaborative workshop model, stylistic lineage, and iconographic strategies—foregrounding his adaptation of scenic topoi to support operatic and dramatic repertories. His preserved works challenge assumptions that early 20th-century scenic practice has vanished beyond study. Instead, they offer insight into performance conventions, painterly methods, and repertory logic in the era of electric lighting and increasing visual sophistication. Dubosq’s scenic designs for operas such as Aida, Lakmé, and La Bohème demonstrate a deep fidelity to original stage directions while illuminating his personal style rooted in the light and color theories of Impressionism.Ultimately, this research responds to the call of Mercedes Viale Ferrero for a historical iconographia theatralis: a theatrical visual lexicon linking dramaturgy, scenography, and audience memory.
FRIS
1
Keywords: Dubosq, Albert; Resounding Libraries: Unfolding Archived Knowledge Through Artistic Research; Scenography; Topos